الأحكا الفقهية اب٤ستفادة من غزكة خيبر بُ اب٤عاملات)دراسة مقارنة(بٕث مقد لنيل د رجة اب٤اجستبّ بُ الشريعة الإسلاميةب رنامج اب٤اجستبّ بُ الشريعة الإسلاميةجامعة سوراكرتا ا﵀مديةAl ahkam Al fiqqiyah Al mustafaadah Min Gozwati Khaibar Fil Muamalh - Rusdi, Halil, Dr. Muchammad Ichsan, Lc., MA, Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
Khaibar is a battle whom Prophet Sallallaahu Alaihi Wasallam is involved to fight against the accursed Jews. This war has a great position in Islamic history whereas Allah azza wa jalla distinguishes between the truth and the falsehood. Beside Allah cuts the roots of Kufur, Khaibar battle has also taught Moslem about some Fiqh laws related with multiple discourses in Islam. They are associated with the cleansing from impurities, worship, human relationship, eating and drinking manner. This thesis discussed about Fiqh law which is related Muamalah/Human relationship as the main subject discussion, citing the opinions from some scholars about the subject, and concludes by mentioning the most preferable opinion according to the author. In writing this thesis the author applied "Istiqro" and "Istimbathy" method, in which the author explored and used some Fiqh law related with human relationship and then gathers and compared all scholar' opinions of Fiqh, includes their evidences. The author also applied At-Tahlily method, where the author described and explaind Fiqh problem and its postulate related with human relationship. And then the author also stated some corrections for the postulate if exists. In the conclusion the author will mention the most preferable opinions and their evidences. Based in the theory that has been written, the author can conclud these following results: "Musaaqoh" and "Muzaaro'ah" are legal or permissible, the illegitimacy of "Riba Fadl" and temporary marriages, the suggestion to conduct wedding party, then the illegitimacy of initiating combat (attacking) against the infidels in particular months (Zulqoidah, Zulhijjah, Muharram, Rojab), the permissible of conducting a truce with the enemy on certain condition which gives benefit for Moslems, the necessity of removing "Ahlul-Zimmah" from Arabian peninsula, and the permissible to fight the infidels without preceded by persuading them to islam if they have got the message of "Da'wah"